Organizational injustice and workplace deviance: The mediating role of employee jealousy in manufacturing and service sectors - Sustiyatik, Enni; Jauhari, Tontowi (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates the effect of organizational injustice including distributive, procedural, and interactional injustice on workplace deviance, with employee jealousy as a mediating variable. The research aims to compare these relationships across two industrial sectors: manufacturing and services in Indonesia. Methodology: A quantitative survey design was employed involving 421 full-time employees from medium to large-sized companies located in East Java, Central Java, and Jakarta. A structured questionnaire using validated scales was distributed using stratified random sampling to ensure balanced sectoral representation. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software (SmartPLS GmbH, Germany), and data preparation was performed using IBM SPSS 26.0. Results: The findings indicate that all three types of injustice significantly increase employee jealousy. Furthermore, jealousy is a strong predictor of workplace deviance. Mediation analysis shows that jealousy significantly mediates the relationships between each dimension of injustice and workplace deviance, with interactional injustice having the strongest overall effect. Conclusions: This study concludes that employee jealousy is a key emotional pathway through which organizational injustice leads to deviant behavior. The results emphasize the importance of fair interpersonal treatment within organizations. Limitations: The study is limited by its cross-sectional design and reliance on self-reported data, which may introduce bias. Contribution: To organizational behavior literature and offers practical insights for human resource management, particularly in emerging economies.